2021
DOI: 10.3389/fcvm.2021.768338
|View full text |Cite
|
Sign up to set email alerts
|

The Deleterious Effects of Impaired Fibrinolysis on Skeletal Development Are Dependent on Fibrin(ogen), but Independent of Interlukin-6

Abstract: Chronic diseases in growing children, such as autoimmune disorders, obesity, and cancer, are hallmarked by musculoskeletal growth disturbances and osteoporosis. Many of the skeletal changes in these children are thought to be secondary to chronic inflammation. Recent studies have likewise suggested that changes in coagulation and fibrinolysis may contribute to musculoskeletal growth disturbances. In prior work, we demonstrated that mice deficient in plasminogen, the principal protease of degrading and clearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In an experimental animal study, it was found that severe osteoporosis, which is fibrinogen-dependent, disorders of bone remodeling units with fibrinogen-mediated osteoclast activation occurred in mice defective in the fibrinogen gene [ 14 ]. However, a study by Cole et al [ 7 ] found impaired fibrinolysis due to fibrinogen deficiency, leading to persistent fibrin deposition, resulting in premature skeletal aging and growth retardation. Increased fibrinogen promotes osteoclast activation, and fibrinogen regulates actin organization through its effects on osteoclast morphology; it not only increases actin organization and enhances bone resorption, but also promotes the formation of M-CSF and RANKL-induced bone resorption, and it alone induces bone resorption in vitro [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an experimental animal study, it was found that severe osteoporosis, which is fibrinogen-dependent, disorders of bone remodeling units with fibrinogen-mediated osteoclast activation occurred in mice defective in the fibrinogen gene [ 14 ]. However, a study by Cole et al [ 7 ] found impaired fibrinolysis due to fibrinogen deficiency, leading to persistent fibrin deposition, resulting in premature skeletal aging and growth retardation. Increased fibrinogen promotes osteoclast activation, and fibrinogen regulates actin organization through its effects on osteoclast morphology; it not only increases actin organization and enhances bone resorption, but also promotes the formation of M-CSF and RANKL-induced bone resorption, and it alone induces bone resorption in vitro [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers mechanistically promote bone resorption and inhibit bone formation, an imbalance that will lead to bone loss and increased fracture risk [ 6 ]. Recent studies have shown that inflammation, coagulation abnormalities, and vascular dysfunction may all contribute to impaired bone development and growth, whereas fibrinolytic enzymes inhibit inflammation and protect blood vessels by reducing fibrinogen accumulation [ 7 ]. This indirectly suggests that fibrinogen plays an essential role in maintaining bone health.…”
Section: Introductionmentioning
confidence: 99%